Development and quality assessment of herb-flavored sweetpotato-chocolate - Hilapad, Marife R. (2014)
This study aimed to formulate and optimize the process of herb-flavored sweetpotato-chocolate spread. Plackett-Burman (PB) variable screening design and Response Surface Methodology (RSM) were used as experimental designs. A 33 factorial experiment arranged in Central Composite Design (CCD) with sweetpotato (125, 150, and 175 g), cocoa tablet (20, 25, and 30g) and basil (5, 10, and 15 g) were used as independent variables.

Packett-Burman variable screening showed that cocoa tablet and basil significantly influenced the acceptability of aroma, flavor, aftertaste, and general acceptability. Buffalo's milk, sweetpotato color, and cocoa tablet significantly affected the color of the product. The third variable considered was sweetpotato. Response surface analysis revealed that basil significantly affected the consistency, flavor, taste, aftertaste, and general acceptability of herb-flavored sweetpotato-chocolate spread. Sweetpotato, cocoa tablet, and basil did not significantly affect the color and aroma of the product.

Superimposed plots of the different variables indicated that the combination of 150-g sweetpotato, 29-g cocoa tablet, and basil was the optimum formulation. It was found negative of Salmonella and E. coli and had low microbial count after six weeks of monitoring. The optimized product had low fat, carbohydrates, and sugar content but high dietary fiber. It also contained calcium and potassium.
Keywords: Sweetpotato spread